2021
DOI: 10.1007/s40272-021-00486-8
|View full text |Cite
|
Sign up to set email alerts
|

Real-Life Use of Biosimilars in Pediatric Inflammatory Bowel Disease: A Nation-Wide Web Survey on Behalf of the SIGENP IBD Working Group

Abstract: ObjectiveThe aim was to assess the awareness and real-life use of biosimilars in inflammatory bowel disease (IBD) among the members of the Italian Society of Pediatric Gastroenterology, Hepatology and Nutrition (SIGENP). Methods An anonymous web survey involving all SIGENP IBD units which can prescribe biosimilars was conducted between July 1st and December 1st, 2020. The questionnaire included 18 questions addressing the most relevant aspects of biosimilars in pediatric IBD, i.e., advantages, disadvantages, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Biosimilars offer a more advantageous costing and reimbursement strategy, with price cuts ranging from 25 to 70% in Europe when compared to originator products ( Brodszky et al, 2016 ). More than 90% of respondents in the previously cited Italian survey believed biosimilars to be cost-effective, with cost savings being the most important benefit of using biosimilars ( Dipasquale et al, 2021 ). If the cost savings from the use of biosimilars were used to fund more biological treatments, several more IBD patients could be treated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biosimilars offer a more advantageous costing and reimbursement strategy, with price cuts ranging from 25 to 70% in Europe when compared to originator products ( Brodszky et al, 2016 ). More than 90% of respondents in the previously cited Italian survey believed biosimilars to be cost-effective, with cost savings being the most important benefit of using biosimilars ( Dipasquale et al, 2021 ). If the cost savings from the use of biosimilars were used to fund more biological treatments, several more IBD patients could be treated.…”
Section: Discussionmentioning
confidence: 99%
“…CT-P13 can be regarded as a good alternative to the originator for induction and maintenance of remission in children with IBD, according to the European Society for Pediatric Gastroenterology, Hepatology, and Nutrition (ESPGHAN) Pediatric IBD Porto Group ( de Ridder et al, 2015 ; de Ridder et al, 2019 ). A recent nationwide web survey conducted in Italy showed that most pediatric IBD experts have good knowledge about biosimilars, with awareness of similar efficacy and safety in comparison to the originator ( Dipasquale et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…57,58 A more recent web survey revealed that pediatric IBD experts in Italy have a good level of knowledge on biosimilar use advantages, disadvantages, costs, and traceability. 59 The increasing confidence in biosimilar use may be linked to the growing post-marketing studies and the dissemination of real-world data. Patient education is also an important aspect of the acceptance of biosimilar treatment.…”
Section: Knowledge On Biosimilar Usementioning
confidence: 99%